Uma nova espécie de Brachycephalus (Anura, Brachycephalidae) do estado do Rio de Janeiro - Pombal Jr., José P.; Izecksohn, Eugenio (Papéis Avulsos de Zoologia, 2011)
A new species of Brachycephalus is described from Sacra Família do Tinguá, municipality of Engenheiro Paulo de Frontin, State of Rio de Janeiro, Atlantic Rain Forest. Brachycephalus margaritatus sp. nov. is characterized by large size (SVL 15.0 to 18.9 mm), orange color in life and cream to grayish cream in preservative, well developed dorsal plates with lateral edges curved down, and scattered bulges on upper surfaces of the body. The geographic distribution of B. margaritatus, B. ephippium, and B. garbeanus are provided.